SENSITIVITY TEST OF DOUBLE ANTIBODY SANDWICH ENZYME LINKED IMMUNOSORBENT ASSAY (DAS-ELISA) TO DETECT FOOT ROOT DISEASE (Phytophthora capsici L) IN PEPPER (Piper nigrum L) - Hasan Syamsul Ulum; Iman Suswanto; Sarbino . (Fakultas Pertanian Universitas Tanjungpura, 2019)
Phytophthora capsici is the causal agent of foot rot, the most destructive disease of pepper in Indonesia and difficult to control. DAS-ELISA test to protect Phytophthora antigens based on antibodies that are very useful for protected plants can only be used up to the genus. This study was aimed to determine the sensitivity of Double Antibody Sandwich Enzyme Linked Immunosorbent Assay (DAS-ELISA) to detect stem rot disease (Phytophthora capsici) in each part of pepper plants (leaves, stems, and pure isolats) with different serial dilutions.The study was done at Laboratorium Balai Karantina Pertanian Kelas I Pontianak. The sensitivity limit for each sample part of the pepper plant was tested through the dilution stage of the plant extract. The results of the sensitivity limits for each sample are different. Samples of the leaves and stems of pepper plants showed positive results of Phytopththora capsici at dilution rates of 100 and 10-1. Whereas in pure isolats positive results of P. capsici were detected until the dilution rate of 10-3. Keywords : Phytophthora capsici, ELISA, dilution